Hubungan Faktor Ekonomi Terhadap Pemilihan Pengobatan pasien Fraktur - Eka Yuliani; Sri Maryuni; Mario Martini (Universitas Mitra Indonesia, 2020)
Fractures or often called fractures are the interruption of continuity of bone tissue and cartilage. Most fractures are caused by injury, trauma where there is excessive pressure on the bone. Fracture treatment consists of being a medical treatment and traditional medicine.The choice of traditional fracture treatment will have a hazard to the patient itself. One of the factors that influence the choice of fracture treatment is economic factors. Economic ability with the level of income and social household members determines how a person chooses and undergoes the desired treatment.The purpose of this study was to determine the Relations Between Economic Factors to the Selection of Treatment in Fracture Patients.Metodology in this study used a analytic correlation with a